The Enrichment Economy: Market Dynamics, Brand Strategy, and Ethics - Dion, Delphine; Pavlyuchenko, Roman; Prokopec; Sonja (Journal of Marketing, 2025)
Rare watches, fine wines and spirits, sports cars, designer sneakers, and many other luxury goods create massive enrichment opportunities for consumers if they resell them on secondary markets. This trend is part of the enrichment economy, a novel form of market arrangement wherein consumers use iconic goods to increase their capital. However, it creates challenges for brands, such as preserving their primary market desirability and avoiding cannibalization. To understand how brands can navigate the enrichment economy, the authors conducted an ethnographic study of the luxury watch industry. They draw on market system dynamics to theorize market processes that sustain a market within the enrichment economy, and they explain the shared discourses, norms, and practices that make the enrichment economy function. This research makes four contributions. First, the authors theorize primary–secondary market dynamics as a novel class of market dynamics. Second, they theorize the new role of luxury brands as enrichment curators. Third, they discuss the ethics of enrichment by highlighting inequalities and risks it creates. Fourth, this research introduces the enrichment strategy as a novel brand strategy that capitalizes on the market dynamics of enrichment. The authors offer recommendations for luxury and nonluxury brands on product portfolio management, customer relationship management, and ethical innovation.